Effect of geographical variation of Echis ocellatus, Naja nigricollis and Bitis arietans venoms on their neutralization by homologous and heterologous antivenoms - Sánchez Brenes, Andrés (2015)
Two antivenoms prepared by using Echis ocellatus, Bitis arietans and Naja nigricollis venoms from different locations in sub-Saharan Africa were compared for their neutralizing ability. Both antivenoms were similarly effective in the neutralization of the venoms of the three species from different locations. However in the case of E. ocellatus venom, antivenom prepared using venom from Nigerian specimens was more effective than antivenom prepared with venom from Cameroon specimens in the neutralization of coagulant activity.